2008
DOI: 10.1071/ea07174
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the published effects of HGP use on beef palatability in steers as measured by objective and sensory testing

Abstract: Abstract. Evidence is presented that suggests strongly that hormone growth promotant (HGP) implantation has a negative effect on beef palatability. This is based on a meta-analysis of results reported in refereed papers that have appeared in the meat-science literature. To be included in this analysis, a paper must have reported results for control samples (no HGP) and treatment samples (HGP) for either objective testing (Warner-Bratzler shear-force) or consumer preference (tenderness score). The paper must al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
(28 reference statements)
3
17
0
Order By: Relevance
“…The use of HGPs has been studied extensively in the database (Thompson et al 2008a;Watson 2008;Watson et al 2008b), and in a range of associated experiments reported elsewhere. The result was an HGP penalty of the order of 3-6 MQ points on meat palatability, depending on the muscle which is further adjusted with aging.…”
Section: Hgp Implantsmentioning
confidence: 99%
“…The use of HGPs has been studied extensively in the database (Thompson et al 2008a;Watson 2008;Watson et al 2008b), and in a range of associated experiments reported elsewhere. The result was an HGP penalty of the order of 3-6 MQ points on meat palatability, depending on the muscle which is further adjusted with aging.…”
Section: Hgp Implantsmentioning
confidence: 99%
“…The effects of such implants on beef palatability have been studied extensively in both the USA and Australia (Thompson et al 2008bWatson 2008;Watson et al 2008c). The NCBA (1996) Beef Palatability Task Force determined that:…”
Section: Advantages Of the Tqm Approach To Assessing Beef Qualitymentioning
confidence: 99%
“…Thompson et al (2008bThompson et al ( , 2008c concluded that the effects of HGP use in reducing flavour, tenderness and overall palatability are much greater in beef from 100% B. indicus cattle than in beef from 50% B. indicus cattle, but that all implant strategies used caused a reduction in meat quality. To assist in the interpretation of the myriad published results, Watson (2008) undertook a meta-analysis of published recent studies in the USA and Australia. He presented evidence that suggests strongly that HGP has a negative effect on eating quality (both sensory and objective laboratory measurements) of beef, especially that of the LD muscle in the striploin.…”
Section: Msa Grading Systemsmentioning
confidence: 99%
“…In contrast, Dikeman (2007) concluded that whilst tenderness was reduced in implanted compared with non-implanted cattle these effects on tenderness were probably not of commercial importance. While there is variation in the interpretation of the literature, a recent metaanalysis of available published results and unpublished data by Watson (2008) clearly showed that when the results from different experiments were considered collectively, M. longissimus dorsi samples from cattle implanted with HGP had greater shear forces and lower tenderness scores than carcasses from non-implanted cattle.…”
Section: Introductionmentioning
confidence: 99%